"Dream of a Republic" - Lebanese Political Parties as "Real Parties" - Thuselt, Christian (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2018)
The thesis deals with Lebanese political parties and their encounters with modernity. The three parties dealt with in this study hold the idea that they are “real” parties that bring about the “real” nation. The objective of the present thesis is to examine what “real” refers to. This study suggests that all three parties are heavily influenced by asymmetrical references to a global normativity. These references are informed by the parties’ experience in Lebanon where they find themselves positioned within global theoretical abstractions and where both, the normativity as well as their abstractions, are felt even in party members’ daily lives. International socio-scientific literature has identified two trends that, as the literature suggests, had evolved since the late twentieth century: First, the nation-state had become less important, and, second, utopian thinking had vanished. The study adds up various panoramas of situations when it became urgent to define one’s identity and claims that important constituents of modernity, such as the individual, the nation, progress, and representing the demos, serve for the parties in question as resources of utopian elements. This becomes evident from official texts and personal self-narrations. Most importantly, Lebanese parties are still taking the nation state as their central reference point and aim at bringing the nation state about because to them it is the legitimate form of organization of society. In consequence, this thesis questions if the alleged weakening of modernity and its intellectual program can be claimed a universal age. It proposes a stronger emphasis on the enforcing, the “pedagogical” (Bhabha) side of representation by researching political parties to make utopian elements visible
Keywords: Lebanon; Political Parties; Christianity in the Middle East; Utopianism; Nation State